Students' Perspective on Collaborative Research-based Learning in Embedded Systems - Wahyudin, Didin; Somantri, Yoyo; Haritman, Erik (Teknologi dan Kejuruan: Jurnal Teknologi, Kejuruan, dan Pengajarannya, 2022)
The Covid-19 pandemic, which has occurred for more than two years, has left various problems in learning. According to the opinion of most teachers and students, learning using an online approach in some courses was less effective. For example, the Embedded Systems course (ES) stimulates students to do product development. Online learning even tended to cause a loss of motivation, especially in applied studies that require adequate time and facilities to do the practicum. Hence there is a need for a learning method that can be a solution to the problems caused by the online approach. In the ES, students are required to understand the not only theory but also practice comprehensively. Therefore, a more sophisticated strategy is necessary. To enable students to see and assess the events that transpired during product development, collaborated research-based learning (CRL) is expected to be a proper method to tackle such problems. With the RL approach, especially for applied subjects such as Embedded Systems, students must be able to innovate so that the learning process encourages them to find real solutions to the faced problems. CRL encourages students to be able to formulate research designs, data collection, practical research, and interpretation of results. CRL engages students in the process and active participation in acquiring reflective knowledge and critical thinking to build their vision. This report presents a preliminary examination of the implementation of CRL in ES to improve students' engagement. The study measure participants’ overview of using project management application in CRL. The study involved 30 students taking the ES. The study finding discovers that the students’ perspective of the CRL approach in ES is suitable during pandemic